Re-Autopsy: Dealing with Almost Impossibility? - Erbaş, Melike; Balcı, Yasemin (The Bulletin of Legal Medicine, 2020)
Performing an autopsy on a body that was autopsied before becomes a very difficult situation; especially for the cases that there is no first autopsy report or any information. Depending on the impossibilities to reach the findings detected in the first autopsy; it becomes a very difficult procedure which is almost impossible. Practically it seems that the important point in such cases is developing trust by sharing the findings and information as much as possible.We would like to discuss the situation on three cases that were re-autopsied after the first autopsy procedures performed abroad.
Keywords: Re-autopsy; second autopsy; methanol intoxication; embalming